Sustainability and innovation in 3D printing: Outlook and trends - Muhammad Ali Saqib; Muhammad Sohail Abbas; Hiroyuki Tanaka (Clean Technologies and Recycling)
The convergence of additive manufacturing (AM), sustainability, and innovation holds significant importance within the framework of Industry 4.0. This article examines the environmentally friendly and sustainable aspects of AM, more commonly referred to as 3D printing, a cutting-edge technology. It describes the fundamentals of AM in addition to its diverse materials, processes, and applications. This paper demonstrates how several 3D printing techniques can revolutionize sustainable production by examining their environmental impacts. The properties, applications, and challenges of sustainable materials, such as biodegradable polymers and recyclable plastics, are thoroughly examined. Additionally, the research explores the implications of 3D printing in domains including renewable energy component fabrication, water and wastewater treatment, and environmental monitoring. In addition, potential pitfalls and challenges associated with sustainable 3D printing are examined, underscoring the criticality of continuous research and advancement in this domain. To effectively align sustainability goals with functional performance requirements, it is imperative to address complexities within fused deposition modeling (FDM) printing processes, including suboptimal bonding and uneven fiber distribution, which can compromise the structural integrity and durability of biodegradable materials. Ongoing research and innovation are essential to overcome these challenges and enhance the viability of biodegradable FDM 3D printing materials for broader applications.